Constraints on agricultural production in the northern uplands of Vietnam - Yen, B.T.; Visser, S.M.; Hoanh, Chu Thai; Stroosnijder, L. (International Mountain Society (IMS) and United Nations University, 2013)
The Northern Uplands of Vietnam form one of the largest ecological regions in the country, characterized by complex biophysical conditions and a high diversity in ethnic minorities, cultures, and farming systems. The Doi moi ("renovation?) program has, since the early 1980s, resulted in significant changes in agriculture production and related economic trends. However, poverty, low agricultural productivity, and land degradation are still major problems. This article illustrates the factors that drive these problems by analyzing agricultural land use in Suoi Con, a small agroforestry watershed in the Northern Uplands. We first identified the current land-use systems and analyzed constraints on agricultural production. The results indicate that although low soil fertility and land degradation are considerable problems, availability of household capital, low technology levels, and land fragmentation are major constraints on agricultural development. These constraints were analyzed from different points of view to identify mismatches between the implementation of top-down government policies and specific conditions that may explain why actual land-use change in the Northern Uplands deviates from the government's development plans. Results of land-use analysis in the Suoi Con watershed suggest that participatory and bottom-up approaches are needed to better understand problems and opportunities in household agricultural production in order to develop appropriate land-use plans and policies.